2017
DOI: 10.1016/j.camwa.2017.07.045
|View full text |Cite
|
Sign up to set email alerts
|

A novel study on subspace migration for imaging of a sound-hard arc

Abstract: In this study, the influence of a test vector selection used in subspace migration to reconstruct the shape of a sound-hard arc in a two-dimensional inverse acoustic problem is considered. In particular, a new mathematical structure of imaging function is constructed in terms of the Bessel functions of the order 0, 1, and 2 of the first kind based on the structure of singular vectors linked to the nonzero singular values of a Multi-Static Response (MSR) matrix. This structure indicates that imaging performance… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…Throughout several researches [4,[20][21][22][23][24], estimation of N(x) at x ∈ Σ is essential to obtain good result. Unfortunately, we have no a priori information of crack, therefore an additional procedure for estimating N(x) is needed, but this requires large computational costs.…”
Section: Further Results: Imaging Of Cracks With Neumann Boundary Conmentioning
confidence: 99%
“…Throughout several researches [4,[20][21][22][23][24], estimation of N(x) at x ∈ Σ is essential to obtain good result. Unfortunately, we have no a priori information of crack, therefore an additional procedure for estimating N(x) is needed, but this requires large computational costs.…”
Section: Further Results: Imaging Of Cracks With Neumann Boundary Conmentioning
confidence: 99%
“…Unfortunately, we have no a priori information on targets A m and R s so that it is impossible to select optimal vectors c n . Thus, with motivation from several researches [14,15,41,42], we adopt following unit vector W(x) instead of (3) such that…”
Section: Remark 1 (Selection Of Test Vector)mentioning
confidence: 99%
“…Kirchhoff and subspace migration are also well-known non-iterative techniques for finding location/shape of unknown inhomogeneities, and they have been applied to a variety of problems (see [38][39][40][41][42][43], for instance). Several studies have confirmed that they are fast, stable, and effective methods for finding various kinds of defects without a priori information of unknown targets.…”
Section: Introductionmentioning
confidence: 99%
“…The following result will be useful for this purpose. Its complete derivation can be found in [28,29].…”
Section: Subspace Migration Without Diagonal Elements Of Msr Matrixmentioning
confidence: 99%
“…Now, we analyze the imaging function in TE polarization. We first recall a useful result derived in [75,76]. Lemma 4.4.…”
Section: Structure Of the Imaging Function: Te Casementioning
confidence: 99%